Feasibility and acceptability of "active" classroom workstations among French university students and lecturers: a pilot study - Sidney Grosprêtre; Gael Ennequin; Sophie Peseux; Laurie Isacco (BMC, 2021)
Abstract Background Sedentary lifestyles plague today's society in terms of physical, psychosocial and cognitive health. Students are particularly at risk because they spend most of their daily time sitting and inactive. The current pedagogical model must be rethought in order to promote students' health, well-being and therefore their success. The objective of this project was to equip one classroom of the sport science department at a university with various active workstations (standing desks, Swiss balls, cycling desks, pedal- or stepper-board) and to evaluate the feasibility and influence of these types of active workstations on the cognitive and psychological factors of the students, and to collect the feedback of lecturers during this experience. Methods Participation in the study was voluntary and students had the opportunity to choose or not to use an active workstation during lectures. A total of 663 students and 14 lecturers completed a survey to evaluate subjective feelings about physical, psycho-cognitive and academic aspects after their first experience with active workstations in the classroom. Results The majority of students and lecturers reported positive effects of active workstations in reducing fatigue, distraction, and boredom. The preferred active workstations were the cycling desks and the Swiss balls. Finally, 89.4% of students favoured using active workstations in future lectures if they had the option, as well as 71% of lecturers, demonstrating the acceptance of such active workstations. Conclusion The present study brings promising results toward a more general implementation of active workstations in universities. Once a familiarisation period is observed, having such workstations in the classroom could help prevent the deleterious effect of sedentary behaviour and promote a more active daily life for the future.